Height estimation using long bone segment length is unlikely to play a role in the routine measurement of healthy preschool children. (7th July 2014) - Elder, Charlotte J; Wright, Neil P
<x xml:space="preserve">Abstract</x> This commentary is on the original article by Weidauer et al. on pages of this issue.